2015
DOI: 10.1128/jvi.02663-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Physiological Gene Targets of the Essential Lytic Replicative Kaposi's Sarcoma-Associated Herpesvirus ORF57 Protein

Abstract: The Kaposi's sarcoma-associated herpesvirus (KSHV) ORF57 gene product is essential for lytic KSHV replication and virion production. Recombinant ORF57-null mutants fail to accumulate several lytic cycle mRNAs at wild-type levels, leading to decreased production of lytic proteins necessary for efficient replication. Several mechanisms by which ORF57 may enhance expression of lytic KSHV mRNAs have been proposed, including mRNA stabilization, mRNA nuclear export, increased polyadenylation, and transcriptional act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…This is in contrast to the gene profile of the KSHV ORF57-dependent genes. In KSHV, while some important late genes belong to the highly ORF57-dependent set, the majority are genes essential for lytic KSHV DNA replication (32). Thus, SM is essential for later steps in the cascade of lytic virus production than ORF57 in KSHV, where the proximate block in ORF57 KO mutants occurs at DNA replication and prior to late gene transcription (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the gene profile of the KSHV ORF57-dependent genes. In KSHV, while some important late genes belong to the highly ORF57-dependent set, the majority are genes essential for lytic KSHV DNA replication (32). Thus, SM is essential for later steps in the cascade of lytic virus production than ORF57 in KSHV, where the proximate block in ORF57 KO mutants occurs at DNA replication and prior to late gene transcription (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all SM-dependent RNAs were late lytic cycle RNAs. Thus, the effect of EBV SM on EBV gene regulation is different from that of its homolog Kaposi's sarcoma-associated herpesvirus (KSHV) ORF57, since ORF57 increases both early and late lytic RNA accumulation as recently shown (32). Since EBV late gene transcription is dependent on DNA replication, this raised the possibility that SM effects on these genes were primarily due to enhanced DNA replication in the presence of SM, although no early genes required for DNA replication were particularly SM dependent ( Fig.…”
Section: Identification Of Ebv Sm-dependent Rna Expression During Ebvmentioning
confidence: 99%
“…If these pathways are indeed redundant, PAN RNA will only be completely destabilized by deletion of the ENE, knockout of ORF57, and inactivation of PABPC1, which will be difficult to establish empirically. Consistent with this idea, PAN RNA levels are only ~1.5–2.5-fold lower in ORF57-deleted virus (Verma et al, 2015; Majerciak et al, 2007) suggesting that PABPC1 overexpression and/or the ENE compensate for ORF57 deletion in the context of viral infection. In contrast, no studies using a virus specifically deleted for the ENE have been reported, so its effects on steady-state levels during viral replication have not been verified.…”
Section: How Does Pan Rna Accumulate To High Levels In Lytic Phasementioning
confidence: 65%
“…Kaposi sarcoma-associated herpesvirus (KSHV, human herpesvirus 8 or HHV8) open reading frame (ORF) 57 is a posttranscriptional regulator of viral gene expression [for review see (Majerciak & Zheng, 2015)] essential for virus gene expression and replication (Majerciak, Pripuzova et al, 2007;Han & Swaminathan, 2006;Verma, Li et al, 2015). A full-length ORF57 protein, naturally occurring as a homodimer (Majerciak, Pripuzova et al, 2015), is composed of 455 amino acid (aa) residues.…”
Section: Introductionmentioning
confidence: 99%